Complex analysis - Howie, John M. ([S.l.] : Springer, 2008)
Complex analysis can be a difficult subject and many introductory texts are just too ambitious for today$1 (Bs students. This book takes a lower starting point than is traditional and concentrates on explaining the key ideas through worked examples and informal explanations, rather than through "dry" theorys